An Improved Hybrid Stable Election Routing Protocol for Large Scale WSNs - Hamad, Lana I. S.; Dag, Tamer; Gucluoglu, Tansal (IEEE, 2021)
In the recent years, wireless sensor networks have become prevalent in a diverse range of applications. Throughout the massive usage of wireless sensor networks, some applications require sensing and/or data collection over large areas of interest. In such applications maximizing the network lifetime thus an efficient energy consumption becomes very critical. In this paper, an improved routing protocol for large-scale WSNs based on the well-known Stable Election Protocol is proposed. With this work, the existing Stable Election Protocol is enhanced by introducing low-cost relay nodes that help to increase the lifetime and the throughput of the network. The communication between the sensor nodes and the base station is established through cluster heads and relay nodes. With the relay nodes, the simulation results show an increase in the network stability period by 34.5% and the throughput by 23%.
Keywords: Wireless Sensor Network; Stable Election Protocol; Relay Nodes; Network Lifetime; Throughput; Engineering; Telecommunications